Edges of Exposure: Toxicology and the Problem of Capacity in Postcolonial Senegal - Tousignant, Noémi (Duke University Press, 2018)
In the industrialized nations of the global North, well-funded agencies like the CDC attend to citizens' health, monitoring and treating for toxic poisons like lead. How do the under-resourced nations of the global South meet such challenges? In Edges of Exposure, Noémi Tousignant traces the work of toxicologists in Senegal as they have sought to warn of and remediate the presence of heavy metals and other poisons in their communities. Situating recent toxic scandals within histories of science and regulation in postcolonial Africa, Tousignant shows how decolonization and structural adjustment have impacted toxicity and toxicology research. Ultimately, as Tousignant reveals, scientists' capacity to conduct research—as determined by material working conditions, levels of public investment, and their creative but not always successful efforts to make visible the harm of toxic poisons—affects their ability to keep equipment, labs, projects, and careers going.

The colonial life of pharmaceuticals: medicines and modernity in Vietnam - Monnais, Laurence (Cambridge University Press, 2019)
Section: ix, 280 pages ; 24 cm
Keywords: =CL

The Values of Versatility: Pharmacists, Plants, and Place in the French (Post)Colonial World - Monnais, Laurence; Tousignant, Noémi (Comparative Studies in Society and History, 2016)
Abstract Colonial pharmacists bio-prospected, acclimatized, chemically screened, and tinkered with plants and their parts, hoping to create products to supply colonial public health care, metropolitan industries, and imperial markets. This article's approach is to examine the trajectories of expertise of two French colonial pharmacists, Franck Guichard and Joseph Kerharo, to illuminate the history of modern medicinal plant research. Both men studied medicinal plants as part of their colonial duties, yet their interests in indigenous therapies exceeded and outlived colonial projects. We take this “overflow” as our point of departure to explore how science transformed medicinal plant values in French colonial and postcolonial contexts. Our focus is on the relationship between value and space—on the processes of conceptual and material (de-/re-)localization through which plant value is calculated, intensified, and distributed. We study and compare these processes in French Indochina and French West Africa where Guichard and Kerharo, respectively, engaged in them most intensively. We show that their engagements with matter, value, knowledge, and mobility defy easy categorizations of medicinal plant science as either extractive or neo-traditionalist. By eschewing simple equations of scientists' motivations with political projects and knowledge-production, we argue that approaching plant medicine through trajectories of expertise opens up grounds for finer analyses of how colonial power and projects, and their legacies, shaped scientific activity.
Keywords: =CL

Capacity as history and horizon: infrastructure, autonomy and future in African health science and care - Geissler, P. Wenzel; Tousignant, Noémi (Canadian Journal of African Studies / Revue canadienne des études africaines, 2016)
_eprint: https://doi.org/10.1080/00083968.2016.1267653
Keywords: =CL

Un devoir citoyen? La qualité du médicament entre privé, public et global au Sénégal - Tousignant, Noémi (Vers une pharmaceuticalisation de la société?: Le médicament comme objet social, 2016)
Au moment où le médicament dépasse les frontières nationales et celles de la médecine thérapeutique, il est essentiel de s’interroger sur les nouveaux espaces sociaux dont il redéfinit les limites. Cet ouvrage présente les effets sociaux du médicament à partir du brouillage et du déplacement de trois de ces frontières, celles entre le normal et le pathologique, entre l’inclusion et l’exclusion sociale, entre la nature et la culture. L’extension du domaine pharmaceutique s’est réalisée de manière inédite à l’échelle planétaire par la diffusion des médicaments et des essais cliniques, mais aussi sur les plans plus quotidiens et individuels de la vie sociale : travail, relations sexuelles, réussites scolaires. L’élargissement de l’usage des médicaments et les usages non médicaux montrent aujourd’hui combien le médicament échappe au seul contrôle médical. Le terme « pharmaceuticalisation » désigne précisément la façon dont des moments de la vie deviennent des opportunités pour l’industrie pharmaceutique. Le médicament est toutefois, comme le montrent les contributions de cet ouvrage, plus complexe qu’un simple objet pharmaceutique. Il est plus particulièrement analysé dans ce livre comme un objet permettant de faire évoluer non seulement les frontières du normal et du pathologique, mais aussi celles de l’inclusion et de l’exclusion sociale, sans nécessairement passer par le pouvoir médical. L’évolution technologique de ces dernières années et les effets matériels du médicament invitent également à étudier comment celui-ci contribue à faire évoluer la frontière entre nature et culture. Les textes rassemblés dans cet ouvrage, issus de l’anthropologie, de l’histoire et de la sociologie, présentent ces nouvelles frontières du médicament comme objet social dans les sociétés du Nord ou du Sud, à partir de problèmes liés à la santé mentale, au tabagisme, au VIH ou au cholestérol.
Keywords: =CL

Traces of the Future: An Archaeology of Medical Science in Africa - Geissler, Paul Wenzel; Lachenal, Guillaume; Manton, John; Tousignant, Noémi (University of Chicago Press, 2017)
This book presents a close look at the vestiges of twentieth-century medical work at five key sites in Africa: Senegal, Nigeria, Cameroon, Kenya, and Tanzania. The authors aim to understand the afterlife of scientific institutions and practices and the “aftertime” of scientific modernity and its attendant visions of progress and transformation. Straightforward scholarly work is juxtaposed here with altogether more experimental approaches to fieldwork and analysis, including interview fragments; brief, reflective essays; and a rich photographic archive. The result is an unprecedented view of the lingering traces of medical science from Africa’s past.
Keywords: =CL